(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى دراسة واقع الأنشطة التربوية والصعوبات التي تعترض تنفيذ هذه الأنشطة وأثرها على التحصيل. وكان من نتائج هذا البحث: أ - حصر الصعوبات التي تعترض تنفيذ الأنشطة المدرسية ومن أهمها: - أكد 92%من أفراد العينة عدم وجود حصص خاصة للأنشطة المدرسية - أكد 80% من أفراد العينة عدم وجود أماكن مخصصة للأنشطة المدرسية. - أكد 72%من أفراد العينة عدم مراعاة المناهج للأنشطة المدرسية. ب- وقد خلص البحث إلى المقترحات الآتية: - ضرورة النظر في إمكانية أن تأخذ الأنشطة دورها في المنهج والمكان. - ضرورة تخصيص مشرف خاص للأنشطة المدرسية في كل مدرسة. - زيادة توعية التلاميذ وأولياء الأمور والمعلمين بالعلاقة الوثيقة بين الأنشطة والتحصيل . The goal of this research is to study the reality of educational activities, the difficulties encountered in implementing them, and their impact on achievement. The results of this research are as follows: A- identifying difficulties encountered in the implementation of school activities, the most important of which are: - 92% of participants have maintained the absence of special classes for school activities - 80% of participants have indicted lack of facilities for educational activities. - 72% of participants have stressed the fact that the school curriculum does not take educational activities into account. B- This research has proposed the following recommendations: - these activities should play their role in the curriculum and facilities. - an expert supervisor on school activities should be appointed in every school. - Increasing students’, parents’, and teachers’ awareness of the close relationship between activities and academic achievement.